Identifikasi Tingkat Self-Efficacy dalam Literasi Digital pada Generasi Z pada Mahasiswa Perguruan Tinggi - Rayendra, Rayendra; Anugrah, Septriyan; Hendri, Nofri; Austin, Diah Anggraini; Hardika, Jodi (Pedagogi: Jurnal Ilmu Pendidikan, 2025)
Current students need to be aware that self-efficacy in digital literacy is essential to ensure openness to technology and to possess the competence to manage available information. Digital literacy is related to the skills required to live, learn, and work in a digital society. Students who have self-efficacy in digital literacy skills will be able to strategically use technology to find and evaluate information, connect and collaborate with others, produce and share content, and use the internet and technology to achieve various personal, academic, and professional goals. This research is conducted in the form of a quantitative approach using Two-way ANOVA data analysis. The aim of this research is to describe self-efficacy in digital literacy skills among Generation Z students and the use of information and communication technology in learning.